Capital accumulation and economic growth in a small open economy - Turnovsky, Stephen J. (Cambridge, UK ; New York : Cambridge University Press, 2009)
Economic growth is an issue of primary concern to policy makers in both developed and developing economies. As a consequence, growth theory has long occupied a central role in economics. In this book, renowned growth theorist Stephen J. Turnovsky investigates the process of economic growth in a small open economy, showing that it is sensitive to the productive structure of the economy. The book comprises three parts, beginning with models where the only intertemporally viable equilibrium is one in which the economy is always on its balanced growth path. Empirical evidence suggests relatively slow speeds of convergence so the second part of the book looks at several alternative ways in which transitional dynamics may be introduced. In the third and final part, the author applies the growth model to the issue of foreign aid, focusing specifically on whether aid should be untied or tied to the accumulation of public capital.
1. Introduction and brief overview -- 2. Basic growth model with fixed labor supply -- 3. Basic growth model with endogenous labor supply -- 4. Transitional dynamics and endogenous growth in one-sector models -- 5. Two-sector growth models -- 6. Non-scale growth models -- 7. Basic model of foreign aid -- 8. Foreign aid, capital accumulation, and economic growth: some extensions.
Includes bibliographical references (pages 226-234) and index.
Added to collection customer.56279.3
Keywords: Saving and investment -- Developing countries -- Econometric models; Endogenous growth (Economics) -- Developing countries -- Econometric models; Economic development -- Developing countries -- Econometric models; BUSINESS & ECONOMICS -- Finance; Economic development -- Econometric models; Saving and investment -- Econometric models; Developing countries; Wirtschaftswachstum; Makroökonomisches Modell; Kapitalbildung; Kleinstaat